William J. Spillman and the birth of agricultural economics - Carlson, Laurie M., 1952- (Missouri biography series., 2005)
"Biography of William J. Spillman, scientist and educator for the United States Department of Agriculture. Explores Spillman's role in the development of the agricultural economics, the agricultural New Deal, genetics research, agricultural education and the Cooperative Extension Service, the post-World War I overproduction crisis, and the Law of Diminishing Returns"--Provided by publisher.